2012
DOI: 10.1590/s0102-09352012000600038
|View full text |Cite
|
Sign up to set email alerts
|

Quantidade de metionina+cistina digestível para poedeiras semipesadas de 75 a 91 semanas de idade

Abstract: 0.132, 0.173, 0.215, in order to provide 0.588, 0.628, 0.669, 0.709 and 0.750% methionine + cystine in the diet. The inclusion of methionine + cystine followed, respectively, the proportions of 67, 72, 77, 81 and 86% with

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 9 publications
2
3
0
1
Order By: Relevance
“…The lower yield of birds fed diets formulated as recommended by Rostagno et al (2011) The different bases for diet formulation (total amino acids vs digestible amino acids) and the methionine plus cystine levels (Rostagno et al, 2011) were not able to significantly affect the feed intake of animals. The lack of significant difference (P > 0.05) in feed intake in this study corroborates the results found in other studies that evaluated the levels of methionine plus cystine for laying hens (Sá et al, 2007;Cupertino et al, 2009;Varela, 2009;Polese et al, 2012).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The lower yield of birds fed diets formulated as recommended by Rostagno et al (2011) The different bases for diet formulation (total amino acids vs digestible amino acids) and the methionine plus cystine levels (Rostagno et al, 2011) were not able to significantly affect the feed intake of animals. The lack of significant difference (P > 0.05) in feed intake in this study corroborates the results found in other studies that evaluated the levels of methionine plus cystine for laying hens (Sá et al, 2007;Cupertino et al, 2009;Varela, 2009;Polese et al, 2012).…”
Section: Resultssupporting
confidence: 92%
“…neither by the Dunnet test, nor by linear or quadratic regression analysis (Table 3). These data corroborate previous studies in which methionine plus cystine have also not affected egg quality (Jordão Filho et al, 2006;Sá et al, 2007;Varela, 2009;Polese et al, 2012). It is possible that the dietary levels of this study were not sufficient to cause significant changes in the quality of internal and external components of eggs.…”
Section: Resultssupporting
confidence: 91%
“…An estimated level of iMetCys of 1031 mg/hen•day (Figure 3) may be necessary to attain EP greater than 80% in H&N Brown SCLH between 8 and 20 weeks of production (99-111 weeks old). This iMetCys level is higher than that recommended by Schmidt et al (2009b), Polese et al (2012), Carvalho (2012, Hy-Line (2014), and Rostagno et al (2017) to maximize EP of SCLH, who reported 786 mg/hen•day for the Lohmann Brown (79-95 weeks old) and 655 mg/hen•day for Shaver Brown (75-91 weeks old), 835 mg/hen•day for Hy-Line W-36 (79-95 weeks old), 599 mg/hen•day for Hy-Line Brown, and 858 mg/hen•day for laying-hens brown eggs with medium-superior performance in the first production cycle, respectively. Methionine + Cysteine is essential for protein synthesis and plays several roles in the body metabolism as methyl group and sulfur donor, participating in protein deposition (Carvalho, 2017;Castro et al, 2020).…”
Section: Ann Model Of Egg Productionmentioning
confidence: 57%
“…A total of 2300 records (23 treatments × five replicates × 20 weeks) were added during the fieldwork. The EAA ranges in the experimental design were established to include the levels for second-cycle hens in commercial genetic lines available in the literature (Schmidt et al, 2009a(Schmidt et al, , 2009b(Schmidt et al, , 2010Schneider, 2011;Polese et al, 2012;Agustini et al, 2014;Hy-Line, 2014) and levels recommended by Rostagno et al (2011) and Rostagno et al (2017) for laying-hen brown eggs with medium-superior performance in the first production cycle.…”
Section: Experimental Designmentioning
confidence: 99%
“…Silva et al (14) também observaram efeito residual na produção de ovos quando se elevou o nível de lisina na fase de uma a seis semanas de idade. O efeito da suplementação de metionina sobre a produção de ovos de poedeiras comerciais em diversas fases de produção já foi relatado por diversos autores (15)(16)(17)(18) . Portanto, a suplementação de metionina é tão importante na fase de produção quanto na fase de cria, mantendo um efeito residual sobre a produção de ovos posteriormente na fase de produção.…”
Section: Resultsunclassified